PENGARUH BRAND IMAGE DAN FASILITAS TERHADAP KEPUTUSAN MENGINAP TAMU DI HARRIS HOTEL BATAM CENTER - Gilang Febriyangga; Nidia Wulansari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Batam City is one of the tourism destinations in, looking at the amount of data on the number of hotels available in Batam City, of course this greatly influences the occupancy rate of hotel rooms in Batam City. One of the hotels in Batam City is HARRIS Hotel Batam Center, this hotel is one of the 4 star hotels in Batam City. This hotel is one of the hotels that is popular with tourists. However, based on observations made by researchers, data were obtained relating to the achievement of occupancy in July 2022 - June 2023, this is the achievement of the target and the average room occupancy rate at the HARRIS Hotel Batam Center experiences fluctuations each month. The aim of this research is to analyze the influence of Brand Image and Facilities on guests' decision to stay at HARRIS Hotel Batam Center. This type of research is quantitative research with a causal associative approach (cause and effect) using survey methods. With a sample size of 98 people using purposive sampling. The data analysis technique used is multiple linear regression analysis by analyzing the influence of brand image and facilities on guests' stay decisions, both jointly (simultaneously) and their individual influence (partial). The research results show that: Brand Image and Facilities show a significant influence together (simultaneously) on guests' decision to stay at HARRIS Hotel Batam Center.Keywords: Brand Image, Facilities, Staying Decision, Hotel